2006
DOI: 10.1002/jcb.20765
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus pulposus cells express HIF-1α under normoxic culture conditions: A metabolic adaptation to the intervertebral disc microenvironment

Abstract: Nucleus pulposus (NP) cells of the intervertebral disc reside in an environment that has a limited vascular supply and generate energy through anaerobic glycolysis. The goal of the present study was to examine the expression and regulation of HIF-1alpha, a transcription factor that regulates oxidative metabolism in nucleus pulposus cells. Nucleus pulposus cells were isolated from rat, human, and sheep disc and maintained at either 21% or 2% oxygen for various time periods. Cells were also treated with desferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
266
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 230 publications
(275 citation statements)
references
References 22 publications
8
266
1
Order By: Relevance
“…Rat and human NP cells were isolated using a method previously reported by Risbud et al 7 Human NP cells were isolated from surgically discarded, magnetic resonance imaging-graded tissue samples. Collection of animal and human tissues for cell isolation was performed as per approved protocols by Jefferson's IACUC and IRB, respectively.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat and human NP cells were isolated using a method previously reported by Risbud et al 7 Human NP cells were isolated from surgically discarded, magnetic resonance imaging-graded tissue samples. Collection of animal and human tissues for cell isolation was performed as per approved protocols by Jefferson's IACUC and IRB, respectively.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…[2][3][4][5] NP cells adapt to this hypoxic niche by modulating a key transcription factor, HIF1A (hypoxia inducible factor 1 a subunit), to promote cell survival, matrix synthesis, and to regulate glycolytic metabolism. [6][7][8][9][10][11][12][13] A recent study using NP-specific conditional Hif1a knockout mice also shows that HIF1A is required for postnatal NP cell survival in vivo. 14 Autophagy is a highly conserved cellular process where organelles and cytosolic proteins are encapsulated within target of rapamycin [serine/threonine kinase]) resulting in increased autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of glycolysis is mediated by hypoxia-inducible factor 1␣ (HIF-1␣), a key transcription factor that is expressed by the nucleus pulposus cells (8). Unlike other skeletal cells such as chondrocytes, in the nucleus pulposus there is normoxic stabilization of this otherwise oxygen-labile protein (6,9). Moreover, despite an absence of HIF-1␣ protein induction in hypoxia, an increase in its transcriptional activity was seen (6,9).…”
mentioning
confidence: 99%
“…Unlike other skeletal cells such as chondrocytes, in the nucleus pulposus there is normoxic stabilization of this otherwise oxygen-labile protein (6,9). Moreover, despite an absence of HIF-1␣ protein induction in hypoxia, an increase in its transcriptional activity was seen (6,9). In a recent study of nucleus pulposus cells, Agrawal et al demonstrated that this transcription factor controlled both glycolysis and matrix synthesis (6).…”
mentioning
confidence: 99%
“…Isolation of NP Cells, Cell Treatments, and Hypoxic CultureRat and human NP cells were isolated and characterized as reported earlier (5). T/C-28, a human chondrocyte line, was kindly provided by Dr. Mary Goldring (Hospital for Special Surgery, Weill Cornell Medical College, New York) (24).…”
Section: Methodsmentioning
confidence: 99%